Synthesis and antioxidant evaluation of some new pyridines - Gouda, Moustafa Ahmed; Helal, Mohamed Hamdy (European Journal of Chemistry, 2015)
One-pot condensation of malononitrile (1), 4-methylpentan-2-one (2), aryl carboxaldehyde (3a-f) and ammonium acetate in ethanol afforded 2-amino-5-isopropyl-4-(4-aryl)-6-methylnicotinonitriles (4a-f). The antioxidant activity of the new synthesized compounds was evaluated and the result showed all compound exhibited weak anti-oxidant activities.